Preparation of flame retardant epoxyacrylate-based adhesive formulations for textile applications - YILDIZ, ZEHRA (TAYLOR & FRANCIS LTD, 2016)
In this research, UV-curable acrylated epoxy-based oligomer adhesive formulations containing vinylphosphonic acid (VPA) were prepared to adhere cord fabrics onto the rubber surfaces. In order to enhance the peel strength between cord and rubber, an alkali treatment was applied onto the cord fabrics prior to the adhesive application process. Adhesive formulations and alkali-treated cords were characterized by Fourier transform infrared (FTIR) spectroscopy. By changing the VPA ratio in adhesive formulation, peel strength, flame retardancy, and thermal properties were evaluated. Results proved that the 10% VPA-included adhesive formulation provided highest char yield values supporting the flame retardancy property and the highest peel strength value of 50.8N/cm between the cord fabric and rubber surfaces.
Keywords: Epoxy acrylate; UV-curing; cord fabric; vinylphosphonic acid; alkali treatment; flame retardant; adhesion; SURFACE MODIFICATION; EPOXY ACRYLATE; UV; POLY(ETHYLENE-TEREPHTHALATE); CRYSTALLIZATION; HYDROLYSIS; ACID; PET